Defining the content of dedicated financial education for natural disaster recovery and climate change adaptation - Villalba-Romero, Felix; Callejón-Gil, Ángela; Salas-Compás, María Belén (My University, 2024)
This paper aims to contribute to the development of possible contents that define the framework of a Financial Education for Disaster Recovery and Climate Change Adaptation (FE-DRCCA).
Keywords: Catástrofes - Aspectos económicos; Disaster recovery; Climate adaptation; Educational framework; Financial instruments